Competitiveness of an enterprise under a flexible manufacturing system. Manufacturing strategy and flexibility - Case study - داود, غسان قاسم; اسماعيل, مصطفى منير (Journal of Economics and Administrative Sciences, 2011)
The research has designed for studying the relationship between manufacturing strategy and its flexibility under the flexible manufacturing system with their reflection on the competitive environmental performance of the firm. To interpret and tackle the problem, a hypothesis has formulated stating that “ the competitive performance of a firm is interpreted by the manufacturing strategy and flexibility which are derived from the firm and its business  strategies under the flexible manufacturing system”. Related literatures with their theoretical dissertations, which enhanced the thoughtful content, have analyzed. An illustrative case study on the flexible manufacturing system at Toyota Motors Corporation working at the global automobile industry is used for supporting the thoughtful linkages and consistency among the variables of the research. It has reached to many conclusions agreed in their essence upon validity of the hypothesis and its logic.